Microbiological culture results and antibiotic sensitivity in renal preservation solution - Mehmet Fatih Yüzbaşıoğlu; Hatice Güzel; Gülay Oyur Çelik; Arzu Tuna; Necla Benlier; Sezgin Topuz; Onur Peker; Alper Boz (Archives of Clinical Nephrology - Peertechz Publications, 2020)
Aim/Background: The aim of this study is to investigate the effects of the solutions used to preserve kidney during transplant surgeries on microbiological culture results and antimicrobial resistance and to evaluate this process from the perspectives of recipients and donors. Methods: This study is a retrospective one, and its data were collected from the files of the transplant patients between October 2009 and June 2018. In order to identify the bacteria, the results of the bacteria cultivation conducted through standard methods were included. Gram-negative bacteria were also included in the study. The antimicrobial susceptibility of the identified bacteria was analysed by means of the disk diffusion method. Only one preservation solution was taken, and the isolated agent was determined to be staphylococcus. Results: When all the results were examined, none of the patient had an infection agent causing clinical infection. This result might be related to the fact that cephalosporin treatment was applied for seven days in all the transplant cases in our clinic. Conclusion: If a good treatment is supported by culture antibiogram, it does not create a problem for the recipient and a successful organ transplant surgery can be performed. In this way, there will be no loss of patients in cases where there are not many organ sources.